Post operative nausea and vomiting after laparoscopic cholecystectomy: comparison of prophylactic effect of dexamethasone with ondansetron (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Postoperative nausea and vomiting after laparoscopic cholecystectomy under general anaesthesia are an unpleasant,distressing effects. Prophylactic use of dexamethesone reducing this effects. Objective This study was designed to compare of dexamethasone and ondansetron for prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy. Methods Sixty patients who underwent laparoscopic cholesystectomy were randomly allocated into two groups. Group A(n=30) patients received 8mg dexamehtasone intravenously and Group B(n=30) patients received 8mg ondansetron intravenously one minute before induction of anaesthesia. All patients received standard general anaesthesia.Perioperative vital signs and postoperative nausea and vomiting were recorded. Results The incidence of nausea was 13.4% in group A, 16.7% in group B(p>0.05) and vomiting was 6.6% in Group A, 13.4% in group B(p>0.05). The difference among the groups was not statistically significant. Conclusion Intravenous dexamethasone was better to ondansetron in prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy. DOI: http://dx.doi.org/10.3329/jbsa.v24i2.19803 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(2): 60-64